Diagnosa Penyakit Chikungunya Menggunakan Metode Certainty Factor - Ikhsan Arif; Achmad Fauzi; Rusmin Saragih (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Chikungunya is a disease caused by the Chikungunya virus (CHIKV) transmitted by Aedes aegypti and Aedes albopictus mosquitoes. Some of the symptoms are sudden fever, chills, pain in the joints, muscle pain in the neck, shoulders and limbs, rash. Treatment of sufferers is aimed at complaints and symptoms that arise and the drugs given are generally only to relieve existing symptoms, such as giving Antipyretic drugs to relieve fever, Antiemetic drugs to relieve nausea / vomiting, or Analgetics to relieve joint pain only, from these problems many people also do not understand the handling of chikungunya disease, therefore it is necessary to have a system that can collect information to collect information and conduct counseling activities on the treatment of Chikungunya disease to the general public and especially to the elderly to provide knowledge about Chikungunya disease using the Certainty Factor method. The purpose of this research is to provide information and knowledge to the public about Chikungunya Disease Treatment and the Elderly know the medicine for Chikungunya Disease treatment. From the results of applying the certainty factor method to diagnose chikungunya disease, it can be obtained that the diagnosis result is acute chikungunya disease with a confidence level of 95.19%.